THE USE OF INFLUENCER ADVERTISEMENTS ON TELEVISION AND THE EXTENT OF CONSUMER RESPONSE TO THEM (AN EXPLORATORY STUDY) - Afnan Mohammed Shaban (Academy Review)
The research aims to study the impact of influencers’ advertisements on television, exploring the consumer’s response to them, their attitude toward the brand, and their purchase intentions. It also seeks to determine the extent to which consumers follow influencers’ advertisements on television, clarify the influence of these advertisements on the consumer’s response and purchasing decision, and examine the relationship between following influencers’ advertisements and the results achieved through brand dissemination. Additionally, the study identifies the reasons behind the influence of influencers’ advertisements on television and examines the public’s preferred methods of presenting this type of advertisement. The study was based on constructing the variables and research model around following influencers and their characteristics, and how these reflect on television advertising among consumers. A descriptive analytical approach was used on a deliberate sample from the city of Baghdad, consisting of individuals who follow influencer advertisements. A questionnaire was used as the research tool to gather opinions and attitudes about the influence of influencer television advertisements on consumer responses. The results indicate that influencers play a role in achieving consumer response and changing their behavior toward the brand, which is linked to factors such as the influence on the brand, its dissemination, and gaining consumer trust. This is further supported by factors such as trust, credibility, attractiveness, and the influencer’s style and language, all of which influence their audience. The study’s hypotheses confirmed that individual characteristics do not affect the response to influencers’ advertisements, while there is a statistically significant correlation between following influencers’ advertisements and consumer decision-making regarding purchases. We expect that this study will be a scientific addition to the field of television advertising, with future studies potentially expanding on this research in other areas within the field.